Cambios del pH salival por el consumo de jugos de frutas industrializados y su efecto en la salud gingival en niños de la Institución Educativa “Isabel La Catòlica” - Rosa Ysla-Cheé; María Pareja Vásquez (Kiru)
Objective: Objective: To determine the relationship between the variation of salivary pH by the consumption of industrialized fruit juices and gingival health in children of the Educational Institution (I.E.) "Isabel La Católica". Material and Method: This is an observational, analytical, cross-sectional study. We evaluated 108 children of both sexes, aged 6 to 8 years. The sample was divided into two groups, a study group that drank industrialized fruit juices and a control group that drank water. A basal salivary pH measurement was performed for both groups with a digital pH meter, and after drinking the industrialized fruit juice or water, it was measured again at intervals of 5 and 10 minutes. The gingival condition was evaluated by Löe Silness Gingival Index and PMA Index. Results: No correlation was found between the Löe Silness Gingival Index and the salivary pHin both groups, p> 0.05. In the study group, basal salivary pH was slightly acidic and a greater fall in pH was observed after 5 minutes of consuming fruit juice, p <0.001. An inverse correlation was found between the gingival index and the salivary pH, in the control group, with a higher gingival index, lower salivary pH. The gingival index in the study group was moderate and in the mild control group. Conclusions: There is no correlation between the gingival health of the children evaluated and the salivary pH associated with the consumption of industrialized fruit juices.